Wpływ przedsiębiorstw na postęp techniczny - Oryl, Kazimierz (Wydział Prawa i Administracji UAM, 1979)
Considerations have been exclusively resticted to conditions of technical progress that ensures growth in labour efficiency on the ground of investment outlays. The outlays can serve both to creation of stable capital in new-built enterprises and also to technical modernization of stable capital in existing enterprises. Assuming that in a socialist system decisions in the sphere of technical progress of macro-economic comprehension have to be taken up by the state it is proved in the elaboration that utilization of enterprises' initiatives is indispensable in a period of intensive development. To this end, it is indispensable, however, such shaping the management system of the national economy to interest enterprises either in lowering outlays or in maximization of earnings and production rentability. To enable enterprises to utilize the achievements of the last technics they must have simultaneously an adequate economic potential at their disposal. It is indispensable then to create big economic units. Being economically strong these units can finance their development and above all they can carry on their own scientific-technical research that guarantees an inflow of adequate inventions and they can also install expensive and technically complicated modern production appliances. There exist, however, different kinds and types of techniques in the economy of each country, which condition tedermined sizes of enterprises. Because both a pre-industrial technique and a technique shaped by the first great industrial evolution exist it is necessary to maintain medium and small enterprises along with big economic units.
Influence of Enterprises on Technical Progress